ANALISIS DETERMINAN FINANCIAL STATEMENT FRAUD DENGAN PENDEKATAN FRAUD DIAMOND (Studi Empiris pada Perusahaan Sektor Manufaktur yang Terdaftar di BEI pada Tahun 2016 – 2018) - Arifiandhita Salsabila Istiyanto; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2021)
This research aims to analyze and provide empirical evidence of the influence of elements of diamond theory fraud on the potential of financial statement fraud. The independent variables of this study are financial stability, financial targets, audit committee financial expertise, ineffective monitoring, rationalization, and capability. The dependent variable of this study is the potential of financial statement fraud.The population used in this study is manufacturing companies listed on the Indonesia Stock Exchange in the period of 2016 – 2018. Sampling was carried out using a purposive sampling method, so that a sample of 74 companies was obtained with 171 research data. The analytical method used is multiple linear regression analysis.The results of this study indicate that financial stability and financial target have a positive and significant effect on the potential of financial statement fraud, the financial expertise of the audit committee and changes in the board of directors have a negative and significant effect on the potential of financial statement fraud, and ineffective monitoring and audit opinion have no effect on the potential of financial statement fraud